Mengungkap Faktor Penghambat dan Solusi Alternatif Pembelajaran Bahasa Arab di SMP IT Al-Hijrah Kelas IX - Ardea Pramesti; Ade Dwi Juliani Ritonga; Muhammad Wildan Fikri Azkia; Sahkholid Nasution (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to explore the challenges in learning Arabic in schools and offer solutions through the Task-Based Learning (TBL) approach, cooperative learning, and the use of digital technology. A qualitative approach is used with data collection techniques in the form of observation, interviews, and documentation. Observations are conducted to observe the practice of learning Arabic in the classroom, interviews are conducted with teachers, students, and parents to explore their perspectives on the challenges faced, while documentation is used to collect supporting data such as syllabus and evaluation results. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the task-based approach and student collaboration are effective in improving speaking and listening skills, as well as increasing student motivation and engagement. This approach creates a dynamic and relevant learning environment, encouraging students to be more active in using Arabic in everyday life.